THE ELABORATION OF OPTIMAL SOCIAL-ORIENTED STRATEGY OF DEVELOPMENT IN THE STRUCTURE OF THE OPERATIONAL MANAGEMENT OF THE ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article is devoted to the topical issues of the process of developing an optimal socially-oriented development strategy in the structure of the enterprise's operational management. The research proposed a scientific approach to the formation of a semantic model of the process of developing a socially-oriented strategy in the structure of operational management of the enterprise, which will consist of two main stages. It was determined that at the first stage of the process of developing a socially-oriented development strategy in the operational management system, a diagnosis of the level of social development of the enterprise is carried out. In addition, we have researched that for a successful diagnosis at the first stage, it is necessary to carry out an analysis of the factors of the internal and external social environment that affect the main determinants of the socially-oriented strategy of the enterprise's development, and an express diagnosis of the level of the socially-oriented strategy of the enterprise's development is carried out, and in parallel, the integral is calculated an indicator of the level of a socially-oriented strategy for the development of the enterprise in the operational management system. Based on the diagnosis of problematic links of social development, the main problems that may arise during its implementation in the practical activities of the enterprise are ranked. At the second stage of the process of developing a socially-oriented strategy for the development of the enterprise, it is proposed to carry out the development and implementation of the strategy directly in the structure of operational management. Thus, the research result of the development of a socially-oriented strategy for the development of the enterprise in the structure of operational management and its consistent implementation will provide it with greater resistance to the influence of the external environment, increasing both the social and general potential of the enterprise, as well as the opportunities for their implementation.
Keywords: strategy, management, enterprise, development, operational management, socio-economic sustainability, optimal social-oriented strategy.